THE CAMBRIAN IMPLOSION. - MAGUIRE, MATTHEW W. (First Things: A Monthly Journal of Religion & Public Life, 2025)
The article focuses on what the author calls the "Cambrian Implosion," a modern reversal of the historical flourishing of life, highlighting the threats posed by technological overreach and declining human and animal populations. Topics include the complex impact of technology on human life, the global decline of biodiversity, and the unprecedented collapse in human fertility and youth well-being.